2016
DOI: 10.5966/sctm.2015-0412
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Spheroids Retain Osteogenic Phenotype Throughα2β1 Signaling

Abstract: The induction of mesenchymal stem cells (MSCs) toward the osteoblastic lineage using osteogenic supplements prior to implantation is one approach under examination to enhance their bone-forming potential. Spheroids formed from induced cells exhibited improved retention of osteogenic markers as a function of integrin binding to cell-secreted extracellular matrix (ECM). These results demonstrate the capacity of spheroidal culture to sustain the mineral-producing phenotype of MSCs, thus enhancing their contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 44 publications
1
63
0
Order By: Relevance
“…25 RGD concentration was not reported, and supraphysiological doses of BMP-2 are associated with numerous complications and high cost. 26 Osteoinduced spheroids retain their osteoblastic markers better than individual MSCs, 6 further motivating the transplantation of MSC spheroids for bone tissue engineering. Herein, we investigated the interplay between RGD ligand density on alginate gels and cell migration from osteoinduced MSC spheroids on their capacity to form mineralized tissue in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 RGD concentration was not reported, and supraphysiological doses of BMP-2 are associated with numerous complications and high cost. 26 Osteoinduced spheroids retain their osteoblastic markers better than individual MSCs, 6 further motivating the transplantation of MSC spheroids for bone tissue engineering. Herein, we investigated the interplay between RGD ligand density on alginate gels and cell migration from osteoinduced MSC spheroids on their capacity to form mineralized tissue in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…11 Unlike conventional cultures, MSC spheroids retain their endogenous ECM, which enhances the persistence of the osteoblastic phenotype compared to individual cells in the absence of soluble osteoinductive cues. 6 ECM retention may prevent cell death upon transplantation, further enhancing the survival and function of MSC spheroids.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic efficacy of MSCs can be increased through their formation into spheroids, three-dimensional aggregates of cells. [5] Compared to monodispersed cells, spheroids exhibit improved cell survival, secrete increased concentrations of bioactive trophic factors, retain their multilineage potential, and represent a more physiologically relevant model of the native cell microenvironment. [6][7][8] Osteoinductive cues such as Bone Morphogenetic Protein-2 (BMP-2) are potent stimuli to induce osteogenic differentiation of MSCs to bone-forming osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…indicated that integrin α 1 interactions predominantly mediated MSC matrix mineralization on collagen I‐coated surfaces . More recently, Murphy etal . showed that MSCs initially cultured with osteoinductive media were able to preserve their osteogenic potential following removal of osteogenic supplements if they were embedded in collagen hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 For instance, the integrin-blocking studies conducted by Salasznyk et al indicated that integrin a 1 interactions predominantly mediated MSC matrix mineralization on collagen I-coated surfaces. 12 More recently, Murphy et al 13 showed that MSCs initially cultured with osteoinductive media were able to preserve their osteogenic potential following removal of osteogenic supplements if they were embedded in collagen hydrogels. However, if cell integrin a 2 b 1 interactions with the hydrogel network were blocked, MSC calcium deposition was significantly reduced.…”
Section: Introductionmentioning
confidence: 99%